2006
DOI: 10.1158/1055-9965.epi-05-0667
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1andCYP1A1Polymorphisms, Tobacco, Air Pollution, and Lung Cancer: A Study in Rural Thailand

Abstract: Objectives: The Lampang Province is situated in the northern region of Thailand. Incidence rates of lung cancer are high for Asian standards, particularly in women. This study was conducted to quantify the risk of lung cancer associated with exposures prevalent in the area and to investigate possible interactions with genetic susceptibility. The presence of several large open-cast coal mines from 1955 close to electricity-generating plants was a particular focus of concern. Methods: Two-hundred and eleven case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…The papers were then reviewed to identify casecontrol studies in Asian populations. A total of 11 case-control studies [36][37][38][39][40][41][42][43][44][45][46] were found. Five studies [36][37][38][39][40] were excluded because there was no exposure assessment and no evidence provided in the study that indoor air pollution from any source made an important contribution to lung cancer.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The papers were then reviewed to identify casecontrol studies in Asian populations. A total of 11 case-control studies [36][37][38][39][40][41][42][43][44][45][46] were found. Five studies [36][37][38][39][40] were excluded because there was no exposure assessment and no evidence provided in the study that indoor air pollution from any source made an important contribution to lung cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies [36][37][38][39][40] were excluded because there was no exposure assessment and no evidence provided in the study that indoor air pollution from any source made an important contribution to lung cancer. The remaining 6 studies [41][42][43][44][45][46] satisfied all inclusion criteria, and data related to study design, geographic location, population setting, case selection, control selection, genotyping method, Hardy-Weinberg equilibrium, type of exposure, exposure assessment, smoking, and number of genotyped cases and controls were extracted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations